Social Entrepreneurship Training Model as Creative Economy Development for Students in Islamic Boarding School - Tri Suminar; Abdul Rahmat; Yudi Siswanto; Lintang Markhamah Watianur Azizah; Riduwan Riduwan; Ratna Juita (Universitas Negeri Semarang, 2022)
Islamic boarding school has the advantage to empower and change the social community. Pesantren has developed to follow the contemporary flow in empowering its students to have competencies of hard skills and soft skills. Graduates of Islamic boarding schools are able to be competitive in the Industrial Era 4.0 with an approach to empower students through social entrepreneurship training in developing entrepreneurship socio- economic creative product. This study aims: (1) Describing the model of social entrepreneurship training, developing a creative economy for students in Islamic boarding school, (2) Describing the management strategy of creative socio-economic entrepreneurship, (3) Describing community participation in agriculturally based industry social entrepreneurship, and (4) The impact of social entrepreneurship on the socio-economic for the community and students. This research method uses a qualitative descriptive design, data collection techniques through in-depth interviews and observations of students and the Clerics. The data validated by triangulating its sources and methods. Data analysis using interactive models. The results are applying a training model based on the needs of students, instructors training experts from stakeholders, and the Industry and Trade Office of Semarang City with a group approach. With the Clerics as the facilitator, the development of product design creativity focused on students. The produced goods are bookcases, Al-Qur'an reading tables, and wooden ashtrays. Entrepreneurial productivity is still limited to help the economic independence of students in the boarding school. Limited production time, in result of most of the time used for learning, product promotion and sales are not quite achieved.